Actividades motoras en casa y la escritura en niños de cinco años de la Institución Educativa Inicial n° 733, Caballococha 2022 - Ruiz Viena, Fiorella Jasmin Azucena (2023)
The research was developed in order to relate motor activities at home and writing in five-year-old children of the Initial Educational Institution n°733 CaballoCocha 2022. This research is non-experimental with correlational study. Five-year-old children of both sexes at Initial Educational Institution No. 733— CaballoCocha 2022 — make up the population under study. This was achieved through observations used as a research method and instrument. Previously, the instruments were validated by expert opinion. As a result, the data showed significant connections between motor activities at home and writing in five-year-old children of Initial Educational Institution n°733 CaballoCocha 2022.